Toxicidade aguda de agrotóxicos e Curva de Sensibilidade de espécies para peixes amazônicos - (:unkn) unknown (Universidade Federal do Amazonas, 2014)
The Amazon has been the target of environmental contamination by the indiscriminate use of pesticides, putting at risk not only the biodiversity and abundance of aquatic organisms, but also the functioning and sustainability of the ecosystem. Little is known about the effects of these substances on Amazonian species, most ecotoxicological studies are developed with species of temperate environment which, in turn, are extrapolated to tropical regions. Furthermore, the maximum permissible values for various substances in use in Brazil are not established by law. The present study was proposed to determine the acute toxicity of four pesticides in five species of Amazonian fish (Carnegiella strigata, Colossoma macropomum, Corydoras schwartzi, Hemigrammus rhodostomus e Paracheirodon axelrodi), allowing properly devise strategies for their protection based on the use of the method of distribution of sensitivity of species and suggest maximum values allowed for each pesticide. First, the Lethal Concentration (LC50) of pesticides was determined, tested individually for the five species. Then, it was determined the concentrations of risk affecting 5% of species (HC5) using the concept of species sensitivity distribution (SED) comparing the data obtained in this study with data from both species of temperate environment obtained from the literature. The maximum allowable values for each pesticide in aquatic environments in the Amazon have been proposed. Based on the results of LC50, deltamethrin showed greater toxicity to fish, followed by glyphosate, imidacloprid and diuron. C. strigata was one of the most sensitive species to exposure to pesticides, whereas C. schwartzi was more resistant, with higher value of LC50. There was no significant difference in the distribution of sensitivity between the Amazonian and temperate species. HC5 values generated with the construction of SDRs have been proposed as starting point for the formulation of standards of water quality in the Amazon region, with regard to the fish group, with the maximum suggested values for deltamethrin, imidacloprid, glyphosate and diuron: 0,242 μg/L, 14.56 μg/L, 177,00 μg/L, 1.27 μg/L, respectively. Therefore, this work is one of the pioneers in conducting toxicity testing in Amazonian fish with pesticides, thus testing contributes to increase the number of ecotoxicological data and can be used as a starting point for discussions involving the determination of maximum allowable values for toxic substances to the aquatic environments of the Amazon.
Keywords: Ecotoxicologia; Toxicologia aquática; Peixes – Amazônia; Agrotóxico; Biodiversidade; Contaminação ambiental; Sustentabilidade; CIÊNCIAS AGRÁRIAS: RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL